2008
DOI: 10.1063/1.2888970
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the surface science of catalysis from single crystals to metal nanoparticles under pressure

Abstract: Vacuum studies of metal single crystal surfaces using electron and molecular beam scattering revealed that the surface atoms relocate when the surface is clean (reconstruction) and when it is covered by adsorbates (adsorbate induced restructuring).It was also discovered that atomic steps and other low coordination surface sites are active for breaking chemical bonds (H-H, O=O, C-H, C=O and C-C) with high reaction probability. Investigations at high reactant pressures using sum frequency generation (SFG) -vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 68 publications
1
43
0
3
Order By: Relevance
“…Although the surface structure of the supported catalyst NPs is complex, in particular for the multicomponent catalysts, a bridge between model systems and practical catalysts made in this work helps to understand the reaction mechanism at the microscopic scale and to construct highly efficient practical nanocatalysts. 84 Furthermore, our work demonstrates that activation in H 2 is a simple but effective route to manipulate the surface architecture of multicomponent catalysts and produce the active sandwich Pt-Ni catalysts. Considering that activation of powdered catalysts in H 2 is the most frequently used pretreatment, the sandwich Pt-TM catalysts produced by the reduction process should be generally present in many Pt-TM systems but are often ignored.…”
Section: Articlementioning
confidence: 82%
“…Although the surface structure of the supported catalyst NPs is complex, in particular for the multicomponent catalysts, a bridge between model systems and practical catalysts made in this work helps to understand the reaction mechanism at the microscopic scale and to construct highly efficient practical nanocatalysts. 84 Furthermore, our work demonstrates that activation in H 2 is a simple but effective route to manipulate the surface architecture of multicomponent catalysts and produce the active sandwich Pt-Ni catalysts. Considering that activation of powdered catalysts in H 2 is the most frequently used pretreatment, the sandwich Pt-TM catalysts produced by the reduction process should be generally present in many Pt-TM systems but are often ignored.…”
Section: Articlementioning
confidence: 82%
“…Using model surfaces, single crystals at first, the evolution of electron, ion and molecular scattering techniques provided atomic and molecular structures, composition and oxidation states and energy transfer information upon adsorption, desorption and scattering of molecules from surfaces [1][2][3][4] . Figure 1 shows the timeline of this development and evolution of surface science.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, nanoparticles have a characteristic that describes the above properties in an integrated manner; we are speaking of confinement of elementary excitations in a nanoparticle. The most important property determined by the confinement of electrons is the discretization of their electronic spectra, which accompanies the increase in the spectral gap width; the broadening of the gap increases when the characteristic size of a nanoparticle decreases [4]. Therefore, it is reasonable to consider the features introduced into the Tamm surface states of nanoparticles by a fundamental property like the electron confinement.…”
Section: Tamm States Of Nanoparticlesmentioning
confidence: 99%
“…Although the catalytic properties of Au (hydrogen-deuterium exchange, the reduction of NO x by using of H 2 , isomerization of paraffins, partial oxidation) had been quite widely studied until the end of the 1980's [1][2][3][4][5][6], it was found that Au is a much less efficient catalyst than the group VIII elements of Mendeleev's table and other transition metals. However, in 1987, it was found by Haruta et al [7][8][9] that small size Au particles increased the activity of CO oxidation dramatically, performing the reaction at temperatures below those of such classical catalysts as Pt [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%